I am currently studying for an abstract algebra final exam. I am trying to disprove the statement "Consider the homomorphism $f: R \rightarrow S$ where R and S are rings. Prove/Disprove: If $a \in R$ is not a unit in $R$, then $s = f(a)$ is NOT a unit in S.

I know this is false because taking $f:\mathbb{Z}_6 \rightarrow \mathbb{Z}_3$,

then f looks like $f([a]_6) = [a]_3$. Then if we let $a = 4$, a is not a unit in $\mathbb{Z}_6$ because it's a zero divisor. However, $a$ IS a unit in $\mathbb{Z}_3$, because $[4]_3 = [1]$, which is a unit.

My trouble is coming in where proving $f:\mathbb{Z}_6 \rightarrow \mathbb{Z}_3$ is indeed a homomorphism.

Here is my attempt:

Let $a, b \in R$. So $a = 6n + r_1$ and $b = 6m + r_2$ for $n, m, r_1, r_2 \in \mathbb{Z}$. So
$f([a]_6 + [b]_6) = f(a) + f(b)$
$f([6n + r_1 + 6m + r_2]_6) = [6n + r_1]_3 + [6m + r_2]_3$

After this line, I'm not exactly sure how to convert the elements in $\mathbb{Z}_6$ to look like elements in $\mathbb{Z}_3$.

If anyone could help me out that would be greatly appreciated.

  • $\begingroup$ Here is an easier counter example: consider the quotient map $\pi : \mathbb{Z} \rightarrow \mathbb{Z}/2\mathbb{Z}$. Then, $5 \in \mathbb{Z}$ is not a unit but $\pi(5) = 1 \in \mathbb{Z}/2\mathbb{Z}$ is. $\endgroup$ – Aniruddh Agarwal Dec 11 '18 at 2:59
  • $\begingroup$ To prove that the map you constructed is a homomorphism, consider using the universal property of quotients. $\endgroup$ – Aniruddh Agarwal Dec 11 '18 at 3:00
  • $\begingroup$ The only way we've learned to prove homomorphisms is show that the function preserves addition and multiplication $\endgroup$ – Mari Dec 11 '18 at 3:01
  • $\begingroup$ You are probably looking at $\mathbb Z_6$ and $\mathbb Z_3$ sets of equivalence classes. (My answer user different viewpoint where $\mathbb Z_6=\{0,1,2,3,4,5\}$. I appologize if that lead to confusion.) So you can simply write $f([a]_6+[b]_6) = f([a+b]_6) = [a+b]_3=[a]_3+[b]_3=f([a]_6)+f([b]_6)$. As pointed out in Aniruddh Agarwal's, the fact that $f$ preserves operation is the easy part when using this viewpoint. What is more relevant here is to show that $f$ is well-defined. $\endgroup$ – Martin Sleziak Dec 11 '18 at 14:08

Your function is given by $f(a)=a\bmod 3$. And you are asking whether $$f(a+_6b)=f(a)+_3f(b).$$ The two operations are given by $a+_6b=(a+b)\bmod 6$ (on $\mathbb Z_6=\{0,1,2,3,4,5\}$ and $a+_3b=(a+b)\bmod3$ (on $\mathbb Z_3=\{0,1,2\}$. So this is equivalent to the question whether $$((a+b)\bmod 6)\bmod 3 = (a\bmod 3+b\bmod 3)\bmod 3.$$ You should be able to show that \begin{align*} ((a+b)\bmod 6)\bmod 3 &= (a+b)\bmod 3\\ (a\bmod 3+b\bmod 3)\bmod 3 &= (a+b)\bmod 3 \end{align*}

Just notice that the two numbers give the same remainder modulo $3$ if their difference is a multiple of $3$, i.e., $$x\bmod 3=y\bmod 3 \qquad\Leftrightarrow\qquad 3\mid x-y.$$ Which is the same as saying that $x$ and $y$ are congruent modulo $3$, if you are familiar with this notion.

So all you can to do is check whether $(a+b)-((a+b)\mod 6)$ and $(a+b)-(a\bmod 3+b\bmod 3)$ are multiples of $3$.

You can use similar arguments to show that $f$ preserves also multiplication, i.e., that $f(a\cdot_6 b)=f(a)\cdot_6 f(b)$. (And, as I mentioned, the whole problem becomes much simpler if you are familiar with basic properties of congruences and modular arithmetic.)

  • $\begingroup$ Thank you very much. Maybe now I have done it correctly: $f([a]_6 + [b]_6) = f(a) + f(b)$ $f([6n + r_1 + 6m + r_2]_6) = [6n + r_1]_3 + [6m + r_2]_3$ $(6(n + m) + r_1 + r_2)mod3 = (6n + r_1)mod3 + (6m + r_2) mod3 $\endgroup$ – Mari Dec 11 '18 at 3:22
  • $\begingroup$ Thank you very much. Maybe now I have done it correctly? $f([a]_6 + [b]_6) = f(a) + f(b)$ $f([6n + r_1 + 6m + r_2]_6) = [6n + r_1]_3 + [6m + r_2]_3$ $(6(n + m) + r_1 + r_2)mod3 = (6n + r_1)mod3 + (6m + r_2) mod3 $ = (6(n + m) + r_1 + r_2)mod3$ This still does not seem right? Have I done something wrong? Does this suffice? $\endgroup$ – Mari Dec 11 '18 at 3:32

Remember to also check that $f$ is well-defined upto choice of representative. Here is how I would write the proof:

Fix $a + 6\mathbb{Z}, b + 6\mathbb{Z} \in \mathbb{Z}/6\mathbb{Z}$. Then,

$$ \begin{align} f((a + 6\mathbb{Z}) + (b + 6\mathbb{Z})) &= f((a + b) + 6\mathbb{Z}) \\ &= (a + b) + 3\mathbb{Z} \\ &= (a + 3\mathbb{Z}) + (b + 3\mathbb{Z}) \\ &= f(a + 6\mathbb{Z}) + f(b + 6\mathbb{Z}) \end{align} $$

You can similarly show that $1$ goes to $1$ and that multiplication is preserved (although the latter follows from the fact that addition is preserved).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.